Re-examining the debt-growth nexus: A grouped fixed-effect approach - Marta Gómez Puig; Simón Sosvilla-Rivero; Inmaculada Martínez-Zarzoso (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
This paper uses panel data for 116 countries over the period 1995-2016 to investigate the heterogeneity of the debt-growth nexus across countries and the factors underlying it. In the first step, the grouped fixed effects (GFE) estimator proposed by Bonhomme and Manresa (2015) is used to classify countries into groups, with group membership being endogenously determined. In the second step, a multinomial logit model is used to explore the drivers of the heterogeneity detected, among them the quality of institutions, the composition of debt-funded public expenditure, the relative public and private indebtedness, and the maturity of debt. Finally, the underlying factors explaining the time-varying impact of public debt on growth in the country groups identified is also investigated.
Keywords: C23; F33; H63; O47; O52; 330; Public debt; economic growth; heterogeneity; grouped fixed-effects; debtgrowthlink; panel data; multinomial logit regression